2006
DOI: 10.1248/bpb.29.119
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein-2 and -4 (BMP-2 and -4) Mediates Fraxetin-Induced Maturation and Differentiation in Human Osteoblast-Like Cell Lines

Abstract: Fraxetin (7,8-dihydroxy-6-methoxy coumarin), a coumarin derivative, was investigated for its effects on differentiation of osteoblasts. By means of alkaline phosphatase (ALP) activity and osteocalcin ELISA assay, we have shown that fraxetin exhibits a significant induction of differentiation in two human osteoblast-like cell lines, MG-63 and hFOB. Alkaline phosphatase and osteocalcin are phenotypic markers for early-stage differentiated osteoblasts and terminally differentiated osteoblasts, respectively. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Several natural or chemical compounds have been reported to induce osteoblast differentiation by induction of BMPs and/or Smad signaling, such as osthole, fraxetin, and myricetin (Kuo et al, 2005(Kuo et al, , 2006Hsu et al, 2007). The present results indicated that BMP-2 mediates 8-PK-induced maturation and differentiation in MC3T3-E1 cells.…”
Section: Involvement Of Runx2 In 8-pk-induced Osteoblast Differentiationsupporting
confidence: 58%
“…Several natural or chemical compounds have been reported to induce osteoblast differentiation by induction of BMPs and/or Smad signaling, such as osthole, fraxetin, and myricetin (Kuo et al, 2005(Kuo et al, , 2006Hsu et al, 2007). The present results indicated that BMP-2 mediates 8-PK-induced maturation and differentiation in MC3T3-E1 cells.…”
Section: Involvement Of Runx2 In 8-pk-induced Osteoblast Differentiationsupporting
confidence: 58%
“…BMP-2 expression in osteoblasts promotes cell maturation and differentiation [40] . As we and others have shown, CGRP increases BMP-2 expression in osteoblasts [41] .…”
Section: Discussionmentioning
confidence: 99%
“…After these transcription factors are phosphorylated on serine residues, they form a complex with a common mediator, SMAD4, and the complex is translocated into the nucleus to activate the transcription of a specific gene [8,9]. Several natural or chemical compounds have been reported to induce osteoblast differentiation by induction of BMP and/or SMAD signaling, such as daidzein, osthole, and fraxetin [11,34,40]. Our study indicates that the production of BMP-2 increases in syringetin-treated MC3T3-E1 and hFOB cells.…”
Section: Discussionmentioning
confidence: 99%